Modeling and optimization criteria of scroll expander integrated into organic Rankine cycle for comparison of R1233zd(E) as an alternative to R245fa. (August 2018) - Yang, Jingye; Sun, Ziyang; Yu, Binbin; Chen, Jiangping
Highlights: A comparative experimental investigation between R1233zd(E) and R245fa was implemented. A semi-empirical expander model was established and validated with experimental data based on 'Generic Algorithm'. Polynomial curve-fittings of dimensionless expander efficiency are conducted for further optimization. Abstract: HFCs are suggested to be banned in 2020 because of high GWP (Global Warming Potential). New type of HFO refrigerant R1233zd(E) is proposed as a drop-in replacement to R245fa for organic Rankine cycle application considering the similar thermo-physical properties. In this paper, a description of previous experimental comparison between two refrigerants is presented in the first section. In the second section, further investigation in expansion procedure is implemented with a semi-empirical expander model, which is validated with experimental data based on 'Genetic Algorithm'. Internal leakage, mechanical friction and heat transfer are presented as main irreversible losses. Input parameters are assigned to mass flow rate, expander rotational speed, supply temperature and exhaust pressure. Supply pressure, exhaust temperature and net power are computed as output results. The maximum deviation between the measured and predicted results are 3.35%, 2.24 K and 6.09% respectively. In the last section, polynomial curve-fittings of dimensionless expander efficiency are conducted for wider prediction of operating range of the expander. Values of filling factor and expander isentropic efficiency are predicted with R 2 = 99.517 % and R 2 = 97.997 % . Curve-fittings of expander efficiency can be integrated into systematic simulation, which is aimed for further optimization of cycle performance to better take advantage of new refrigerants.